1999
DOI: 10.1176/ajp.156.10.1550
|View full text |Cite
|
Sign up to set email alerts
|

Affective Responsiveness in Borderline Personality Disorder: A Psychophysiological Approach

Abstract: The results do not agree with the hypothesis that there is a fundamental, biologically based affective hyperresponsiveness in borderline personality disorder, as is suggested by current theories of affect dysregulation in the disorder. Autonomic underarousal may seriously interfere with a flexible adaptation to environmental stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
147
10
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 19 publications
14
147
10
4
Order By: Relevance
“…From a clinical point of view, BPD patients were described to show affective hyperarousal in response to emotional stressors (Linehan, 1993). In a laboratory setting, however, hyperarousal in response to stressful stimuli has not been clearly demonstrated, either in the present study or in earlier investigations (Herpertz et al, 1999(Herpertz et al, , 2001). …”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…From a clinical point of view, BPD patients were described to show affective hyperarousal in response to emotional stressors (Linehan, 1993). In a laboratory setting, however, hyperarousal in response to stressful stimuli has not been clearly demonstrated, either in the present study or in earlier investigations (Herpertz et al, 1999(Herpertz et al, , 2001). …”
Section: Discussioncontrasting
confidence: 80%
“…The first study of physiological correlates of emotional stress in BPD was conducted by Herpertz et al (1999). They examined 24 female patients with BPD and compared them with 27 normal control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Für andere Autoren steht die emotionale Dysregulation oder die Beziehungsstörung bei der Borderline-Persönlich-keitsstörung im Zentrum der Psychopathologie [37,38]. Ergebnisse von Validitätsstudien der DSM-IV-Kriterien deuten darauf hin, dass das Kriterium «instabile Beziehungen» die höchste diagnostische Effizienz aufweist [39,40].…”
Section: Diskussionunclassified
“…Schmahl et al [7] measured heart rate, blood pressure and skin conductance in BPD patients and found no evidence for hyperarousal in BPD patients as compared to controls. As an explanation for the lowered physiological responses in the study by Herpertz et al [6], the authors suggested the presence of hyporesponsiveness instead of hyperresponsiveness in BPD patients. This hyporesponsiveness in BPD patients might create an openness to emotional stimuli in order to compensate for their feelings of underarousal and emptiness.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Herpertz et al [6] found that when examining levels of heart rate, startle response and skin conductance responses to emotional stimuli, BPD subjects responded by lower physiological arousal as compared to control subjects. Schmahl et al [7] measured heart rate, blood pressure and skin conductance in BPD patients and found no evidence for hyperarousal in BPD patients as compared to controls.…”
Section: Introductionmentioning
confidence: 99%